PENGELOLAAN KEARSIPAN PENGURUSAN, PENGENDALIAN DAN PENATAAN ARSIP KANTOR CAMAT - Ade Kharisma E.42008005 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this research is "Pengelolaan Kearsipan, Pengurusan,Pengendalian, dan Penataaan Arsip Kantor Camat". This research aims to findout about the management of archives relating to the Arrangement,Arrangement Control and district office archives. The study draws on aphenomenon that occurs in the office of district, sub-district office Tekarangparticularly where management of archives at the district office tekarang doesnot comply with the rules set West Kalimantan Governor Decree number 453of 2005 on Procedures for Filing of West Kalimantan provincial government.Records management is one of the activities of management. archival management activities are not going well will certainly hinder any office workrelated to the provision of information quickly and accurately. Someconstraints are commonly encountered in the management and structuring ofthe archive is an employee not understand the maintenance procedures, controland arrangement of records in accordance with applicable regulations so thatrecords maintained by the pickup, then infrastructure unfavorable archivalrecords management so that the maintenance of records is not optimal thoughhaving employees who are competent in the field of archives. This research isa qualitative research using triangulation techniques for data validation.Results from this study is the management of archives relating to themanagement, control and arrangement of records in the Office of the HeadTekarang less than optimal due to the HR field of archives and archivalinfrastructure. Keywords: Management, Handling / Control, Setup, Archive